Enamel hypoplasia in a litter of rats with alloxan-induced diabetes mellitus - Silva-Sousa Yara Teresinha Corrêa; Peres Luiz Cesar; Foss Milton Cesar (Fundação Odontológica de Ribeirão Preto, 2003)
Enamel hypoplasia is an important clinical problem commonly seen in children born to diabetic women. We aimed to characterize the enamel hypoplasia in Wistar rats born to alloxan-induced diabetes mellitus rats. Groups consisted of pregnant rats supplemented (ISDR) or not (NISDR) with insulin and controls, in which sterile saline solution was administered instead of alloxan or insulin. The mandibular incisors of one-month-old rats born to these mothers were analyzed. Whitish defective enamel was found macroscopically in both experimental groups (ISDR = 37.5%, NISDR = 33.3%) but not in the control group. Mild to severe enamel hypoplasia was observed by scanning electron microscopy (ISDR = 93.8%; NISDR = 100%, control = 4.2%). The severity of hypoplasia correlated positively with the maternal level of blood glucose. In conclusion, the intensity of enamel hypoplasia in the teeth of the litter born to alloxan-induced diabetic rats was variable and was dependent on the glycemic level of the pregnant rat.